1998
DOI: 10.1016/s0029-7844(98)00091-x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated Maternal Serum Relaxin Concentrations Throughout Pregnancy in Singleton Gestations After Superovulation

Abstract: In singleton gestations after superovulation, maternal serum relaxin concentrations are significantly higher throughout the second and third trimesters of pregnancy. These differences are independent of the pattern of hCG secretion. It appears that luteal relaxin secretion is controlled by factors in addition to hCG.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(17 citation statements)
references
References 13 publications
1
15
1
Order By: Relevance
“…Similarly, many women who undergo autologous frozen embryo transfer frequently do so in a medicated cycle involving hypothalamic-pituitary suppression. On the other hand, women undergoing ovarian stimulation, IVF and fresh embryo transfer have multiple corpora lutea, and thus, elevated levels of circulating relaxin (Mushayandebvu et al, 1998). Relative to spontaneous conceptions, we anticipate subdued changes in the maternal circulation ('hypodynamic') of women conceiving by ART with absent corpus luteum and circulating relaxin, particularly during early pregnancy, consistent with the rat studies (Conrad and Baker, 2013).…”
Section: Role Of Relaxin In the Cardiovascular Adaptations To Pregnancysupporting
confidence: 78%
“…Similarly, many women who undergo autologous frozen embryo transfer frequently do so in a medicated cycle involving hypothalamic-pituitary suppression. On the other hand, women undergoing ovarian stimulation, IVF and fresh embryo transfer have multiple corpora lutea, and thus, elevated levels of circulating relaxin (Mushayandebvu et al, 1998). Relative to spontaneous conceptions, we anticipate subdued changes in the maternal circulation ('hypodynamic') of women conceiving by ART with absent corpus luteum and circulating relaxin, particularly during early pregnancy, consistent with the rat studies (Conrad and Baker, 2013).…”
Section: Role Of Relaxin In the Cardiovascular Adaptations To Pregnancysupporting
confidence: 78%
“…In animal models, it was shown that the involvement of relaxin in cervical collagenolysis decreased cervical resistance and led to consequent cervical ripening (19). Compared with naturally conceived pregnancies, those conceived through ovulation induction had higher circulating levels of relaxin not only in the first trimester (20) but also in the second and third trimesters (21). Finally, higher relaxin levels observed at the third trimester were significantly associated with PTB (18).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in the presence of a subclinical infection, if endogenous RLN levels were elevated, such as in multifetal pregnancies [13] or in singleton pregnancies after superovulation [14], RLN could significantly affect the outcome of the pregnancy. This is in addition to it being able to cause a sterile inflammatory response in the absence of any infection [16].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, in patients with more than one corpus luteum, as in some twin gestations [13], or in superovulation [14], the higher than normal systemic RLN somehow contributes to PTB, although the mechanism involved is currently unknown. We have shown that the intrauterine expression of RLN is not increased in patients with severe chorioamnionitis, despite significantly increased IL6 expression [15].…”
Section: Introductionmentioning
confidence: 99%